1995
DOI: 10.1111/j.1439-0531.1995.tb00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Catecholamines on the Secretory Function of the Bovine Corpus Luteum

Abstract: ContentsAdrenergic innervation of the ovary is crucial for the corpus luteum (CL) secretory function in many species. Noradrenergic stimulation of the ovary or noradrenaline (NA) treatment causes a prompt increase in progesterone and ovarian oxytocin (OT) secretion during the entire luteal phase. Ths effect is medated via luteal cell 8-recep tors. Their amount correlates with peripheral progesterone concentrations on days 4, 8 and 12 of the oestrous cycle. NA also stimulates progesterone and OT synthesis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In addition, few studies have evaluated the effects of NE on the synthesis of the key ovarian hormones progesterone (P4) and estradiol (E2). Norepinephrine has been previously shown to induce P4 production in the bovine corpus luteum [11,12]. However, the effects of NE in E2 production by ovarian follicular granulosa cells (GCs) have not been demonstrated in mammalian species, despite the known elevation of catecholamine levels in the estrogenic pre-ovulatory phase of the rodent estrous cycle [13] and the presence of high concentrations of NE in the follicular fluid and follicular wall of both, small antral and pre-ovulatory follicles of cows [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, few studies have evaluated the effects of NE on the synthesis of the key ovarian hormones progesterone (P4) and estradiol (E2). Norepinephrine has been previously shown to induce P4 production in the bovine corpus luteum [11,12]. However, the effects of NE in E2 production by ovarian follicular granulosa cells (GCs) have not been demonstrated in mammalian species, despite the known elevation of catecholamine levels in the estrogenic pre-ovulatory phase of the rodent estrous cycle [13] and the presence of high concentrations of NE in the follicular fluid and follicular wall of both, small antral and pre-ovulatory follicles of cows [14].…”
Section: Introductionmentioning
confidence: 99%
“…Accepting this hypothesis, it is possible to explain the prompt CL response to catecholamine challenge in vivo [27,36] in contrast to the response in vitro [5]. Furthermore, when the early stages of CL formation and its importance in early pregnancy are taken into account, this catecholamine mechanism influences CL secretion and supports its normal function, regardless of blood pressure changes in the general circulation [39].…”
mentioning
confidence: 96%
“…Results from studies on other species have suggested that dopamine can affect this process directly through specific dopamine receptors (Clarke et al, 1979;Hilditch & Drew, 1985;Cameron et al, 1992), indirectly through the adrenoceptors by way of a cross-reaction (Weiner, 1985) or finally dopamine can be converted to NA in the process catalysed by dopamine-f-hydroxylase (Levin et al, 1960). Dopamine, which is a precursor for NA, was discovered to be present in bovine corpus luteum (CL) (Battista et al, 1989;Denning-Kendall et al, 1991) and was found to stimulate OT secretion from CL in conscious heifers (Kotwica et al, 1995). NA influences the concomitant secretion of progesterone and ovarian OT during all stages of oestrous cycle in cattle (Kotwica et al, 1991; by acting through the fl-adrenoceptors (Godkin et al, 1977;.…”
Section: Introductionmentioning
confidence: 99%